Dependence of solid oxide fuel cell electrode microstructure parameters on focused ion beam – Scanning electron microscopy resolution. (21st December 2016) - Shimura, Takaaki; Jiao, Zhenjun; Shikazono, Naoki
Abstract: Dependence of microstructure parameters on the resolution of focused ion beam-scanning electron microscopy (FIB-SEM) images was evaluated for nickel-yttria stabilized zirconia (Ni-YSZ) electrode of solid oxide fuel cell (SOFC). Three dimensional microstructure was reconstructed by FIB-SEM images at voxel size of 3 nm which is the highest resolution among the reported SOFC researches. Volume fraction, triple phase boundary (TPB) density and specific surface areas were calculated with various resolutions. Dependences of TPB density and specific surface areas on resolution were clearly shown. Changes of these parameters at high resolution were attributed to the surface roughness caused by the image drift in the scanning electron microscopy imaging. Accurate vales of TPB density and specific surface area were estimated by extrapolation from several values at coarser resolutions and compared with those at typical resolutions which are normally applied in conventional microstructure analysis of SOFC electrodes. The result indicates that the dependence on resolution should be taken into account for the quantitative analysis of microstructure parameters. Highlights: Dependence of SOFC microstructure parameters on resolution was investigated. Three dimensional microstructure was reconstructed with high resolution of 3 nm. TPB density and specific surface areas showed strong dependence on resolution. Accurate values of TPB density and specific surface areas were estimated.